Catalytic Oxidative Depolymerization of Sodium Lignosulfonate into Valuable Esters over CuxO/m‐Sep Catalyst in H2O Solvent Systems. Issue 39 (19th October 2022) - Sheng, Zhiyuan; Shao, Lishu; Zhang, Lin; Zhan, Peng; Wu, Zhiping
Abstract: The catalytic oxidative depolymerization is one of the main means for lignin depolymerization to produce various value‐added chemicals, such as ketones, aldehydes and organic acids, et al. However, the high‐efficiency cleavage of lignin interlinkage is often challenging due to the high recalcitrance of C−C bonds and the weak activity of catalyst. Herein, a series of modified sepiolite (m‐Sep) supported metal oxide catalysts (Mx O/m‐Sep) were prepared by the precipitation method with assistance of ultrasonic wave, and firstly used in the oxidative depolymerization of sodium lignosulfonate (SLS). Three Mx O /m‐Sep catalysts (Cux O, Cox O, and Fex O) were characterized by SEM, TEM, XRD, N2 adsorption‐desorption, FT‐IR, XPS, and O2 ‐TPD to study their microstructure and surface chemical state. The effect of the reaction conditions (temperatures, O2 initial pressure, and time) for the oxidative depolymerization of SLS in H2 O solvent were investigated over Cux O/m‐Sep catalyst, respectively. Correspondingly, the orthogonal experiment was also performed for obtaining the optimal depolymerization conditions. The results indicated the conversion rate of SLS could reach the highest value of 99.2 wt% under 1 MPa O2 at 210 °C for 4 h, and the optimal yield rate of ethyl acetate‐soluble products (EA‐soluble products) was 11.1 wt%. All these EA‐soluble products were analyzed by GC‐MS, and the selective esters including diethyl maleate (18.41 %) and diethyl succinate (22.91 %) could be obtained over Cux O/m‐Sep catalyst under the optimal reaction conditions. In addition, Cox O/m‐Sep and Fex O/m‐Sep also exhibited comparable catalytic performance for SLS. This work developed a new approach for the effective oxidative depolymerization of SLS with low‐cost catalysts and mild conditions, and provided references for the production of lignin‐derived high‐value chemicals. Abstract : A series of modified sepiolite supported metal oxide catalysts (Mx O/m‐Sep) were prepared by the precipitation method with ultrasonic assistance, and used in the oxidative depolymerization of sodium lignosulfonate (SLS). SLS was depolymerized into valuable esters over these catalysts by O2 in water systems, the selective esters including diethyl maleate (18.41 %) and diethyl succinate (22.91 %) was obtained over Cux O/m‐Sep under the optimal reaction conditions.